Dave Hullfish Bailey : Union Pacific: Berlin's Neue Mitte and the Fringes of Las Vegas. - Künstlerhaus Bethanien, Berlin; Philip Morris Kunstförderung, München; Art Center College of Design, Pasadena (Berlin : Künstlerhaus Bethanien, 1999)
The catalogue appears as a documentation of David Hullfish Bailey's residency in 1998 as a grantee of the Philip Morris Kunstförderung Art Sponsership in the international Studio Program.
biog., tent., bibliog. p. 33
Duits
Engels
Exhibition. Dave Hullfish Bailey : Union Pacific : Berlin's Neue Mitte and the Fringes of Las Vegas. Künstlerhaus Bethanien Berlin. 1999 i.s.m. Philip Morris Kunstförderung München & Art Center College of Design Pasadena
boek
Keywords: Bailey, Dave Hullfish; Berlin; Las Vegas